IMPACT OF INSULIN OR INSULIN LIKE GROWTH FACTOR-I ADMINISTRATION DURING MID-LUTEAL PHASE OF ESTROUS CYCLE ON IN VIVO EMBRYO PRODUCTION IN SAHIWAL CATTLE - SHEETAL, S K; PRASAD, S; GUPTA, H P (The Indian Journal of Animal Reproduction, 2022)
On day 5, 6, 7, and 8 (mid-luteal phase) of estrous cycle, two groups of Sahiwal cattle were administered (S.C.) insulin (n=6) or IGF-I (n=6), whereas, another group was kept as untreated control (n=6). The embryos were collected non-surgically on day 7 of superovulatory estrus. In all the groups, the maximum diameter (mm) of largest follicle and 2nd largest follicle was recorded on day 13 of estrous cycle. The number of ovulations, recovered total embryo/ova, transferable embryos, degenerated embryos and unfertilized ova differed (p>0.05) between groups. Insulin-treated cattle had highest (p>0.05) number of total embryo, transferable embryo and recovered blastocyst. In brief, insulin administration during mid-luteal phase of estrous cycle has the potential to improve in vivo embryo production in Sahiwal cattle.